History of Image Digital Formats Using in Information Technology - Alaa Jabbar Qasim; Farah Qasim Ahmed Alyousuf (QALAAI ZANIST SCIENTIFIC JOURNAL, 2021)
An important type of digital media is images, and in this article, we are going to review how images are represented and how they can be manipulated with simple mathematics. This is useful general knowledge for anyone who has a digital camera and a computer, but for many scientists, it is an essential tool. Printed publications use different formats to specify the properties of the information published; Thus, the uses that each type of each publication have been defined. Also, the formats of the digital images have been developed for use with a certain type of images and this article presents the benefits and uses of the different digital image formats.